Error in Students' Thesis Writing: Syntactical and Morphological Error Analysis - Pasaribu, Arsen Nahum; Pasaribu, Tiara K; Hutauruk, Melisa Novriarta; Marbun, Leriana (Budapest International Research and Critics University, 2021)
Research on students' error writing has grown in the last few decades. In general, research on writing errors focuses on the results of students' writing in classes with various writing genres. Students in university also find some obstacle in their English writing, especially for EFL students that write their thesis in English. The students still made errors in their thesis of writing. However, research on errors in thesis writing is relatively unexplored. Therefore this study tries to explore the errors made by students when writing their thesis and factors of error making. This study uses data on ten students’ undergraduate theses, which were randomly selected from 100 student theses from 2018-2021, and used an error analysis framework put forward by (Dulay et al., 1982). The results show that six categories of errors found in the student thesis, namely errors in the use of verbs with 24.54%, errors in the application of prepositions 24.39%, morphological errors 20.12%, errors in using articles 12.58%, errors in writing passive voice 9.45%, and the use of tense selection with 8.92%. Inter-lingual factors cause errors in students' thesis writing. The findings shows that the students in writing thesis still made errors even though they have been guided by the thesis supervisors. Therefore, in teaching academic writing, it is advisable to pay attention to these two factors so that students' writing abilities can improve. Further studies on error analysis in thesis writing are still needed to explore with varied types of errors and more data for analysis.